2013
DOI: 10.1155/2013/459282
|View full text |Cite
|
Sign up to set email alerts
|

Renal Leiomyosarcoma: A Diagnostic Challenge

Abstract: Renal leiomyosarcoma is a very rare tumor that clinically and radiographically mimics more common renal malignancies. The infrequency of the condition makes it very difficult to diagnose. A 70-year-old male smoker presented with months of hematuria, right-sided flank pain, and weight loss. Imaging revealed a 3.8-centimeter renal mass that had characteristics similar to renal cell carcinoma. Initial biopsy of the mass was negative for malignancy. Two months later, subsequent imaging revealed what appeared to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Deletions in the 4q31 and 18q22 regions have been associated with a high metastasis potential and the duplication at 1q21.3 has been identified as an independent prognostic factor for shorter survival times in patients with LMS. On the other hand, a 17q duplication is associated with a long-term disease-free survival and a low risk of metastasis and 1p33-p32.3 duplications were correlated with increased survival rates 3,38 .…”
Section: Genetic and Molecular Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deletions in the 4q31 and 18q22 regions have been associated with a high metastasis potential and the duplication at 1q21.3 has been identified as an independent prognostic factor for shorter survival times in patients with LMS. On the other hand, a 17q duplication is associated with a long-term disease-free survival and a low risk of metastasis and 1p33-p32.3 duplications were correlated with increased survival rates 3,38 .…”
Section: Genetic and Molecular Factorsmentioning
confidence: 99%
“…Valery et al found that a tumor size smaller than 5 cm is associated with a favorable prognosis 3 . In a study conducted by Hakan et al, 2 out of 10 patients enrolled in the research had a tumor measuring less than 5 cm, and they achieved the highest survival rate 25 .…”
Section: Anatomical and Surgical Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcomas typically possess a pseudocapsule, which is often infiltrated by the tumor 3 . The documented biological behaviour of renal leiomyosarcoma is unpredictable which may be due to paucity of extensive literature.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of natural barriers for sarcomas arising from the mesenchymal components, renal sarcomas are able to expand and become large in size. Sarcomas typically possess a pseudocapsule, however, this represents an unreliable barrier and is often infiltrated by the tumor ( 3 ).…”
Section: Introductionmentioning
confidence: 99%